22q11 Deletion Syndrome: A Genetic Subtype of Schizophrenia - Bassett, Anne S. (1999)
Schizophrenia is likely to be caused by several susceptibility genes and may have environmental factors that interact with susceptibility genes and/or nongenetic causes. Recent evidence supports the likelihood that 22q11 Deletion Syndrome (22qDS) represents an identifiable genetic subtype of schizophrenia. 22qDS is an under-recognized genetic syndrome associated with microdeletions on chromosome 22 and a variable expression that often includes mild congenital dysmorphic features, hypernasal speech, and learning difficulties. Initial evidence indicates that a minority of patients with schizophrenia (~2%) may have 22qDS and that prevalence may be somewhat higher in subpopulations with developmental delay. This paper proposes clinical criteria (including facial features, learning disabilities, hypernasal speech, congenital heart defects and other congenital anomalies) to aid in identifying patients with schizophrenia who may have this subtype and outlines features that may increase the index of suspicion for this syndrome. Although no specific causal gene or genes have yet been identified in the deletion region, 22qDS may represent a more homogeneous subtype of schizophrenia. This subtype may serve as a model for neurodevelopmental origins of schizophrenia that could aid in delineating etiologic and pathogenetic mechanisms.